Wyodrębnianie ośrodków odpowiedzialności w zakładach ubezpieczeń działu II - Chmielowiec-Lewczuk, Magdalena (The Singling Out Responsibility Centres in Non Life Insurance Companies, 2005)
The paper presents a problem with singling out responsibility centres in non life insurance companies. It particularly concerns partition of them according to different criteria, adaptation to organizational structure and responsibility accounting.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 313-319